Pengaruh Kepemimpinan dan Lingkungan Kerja Terhadap Kinerja Pegawai dengan Variabel Motivasi Sebagai Intervening: Studi pada Badan Keuangan Daerah Kota Tegal - Achmat Rizkon; Euis Soliha (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of leadership and work environment on employee performance with motivation as an intervening variable at the Regional Financial Agency of Tegal City. Employee performance is an important factor in achieving organizational goals, which is influenced by various aspects, including effective leadership and a supportive work environment. This research uses a census method, with all employees of the Regional Financial Agency of Tegal City as respondents. Data was collected through questionnaires and analyzed using multiple linear regression tests to test the relationship between variables. The research results show that Leadership has an effect on motivation, Work Environment has no effect on motivation, Leadership has no effect on employee performance, Work environment has no effect on employee performance, Motivation has no effect on employee performance, Leadership through motivation has no effect on employee performance, Work Environment through motivation has no effect on employee performance. This indicates that there are other factors outside the variables studied that have a greater influence on employee performance. Therefore, further research is recommended to consider other factors such as organizational culture, reward systems, or employee welfare in order to obtain a more comprehensive understanding of improving employee performance.